Topographically-controlled Deglacial History of the Humber River Basin, Western Newfoundland - Batterson, Martin; Catto, Norm (Géographie physique et Quaternaire, 2001)
AbstractThe Humber River in western Newfoundland flows through a large interior basin, that influenced Late Wisconsinan ice flow from major dispersal centres to the north, in the Long Range Mountains, and to the east in The Topsails. An early southward ice flow from a source to the north covered coastal areas in the western part of the basin. Subsequent regional ice flow was southwestward to northwestward from The Topsails, while south to southwestward flowing ice from the Long Range Mountains occupied the upper Humber River valley. This flow was confluent with ice from The Topsails and moved northwestward toward Bonne Bay. Regional deglaciation began about 13 ka from the inner coast. Ice occupying the Deer Lake valley dammed glacial Lake Howley in the adjacent Grand Lake and Sandy Lake basins to an elevation up to 85 m above present lake levels, which were controlled by drainage through a western outlet feeding into St. George’s Bay. The lake was lowered by exposure of the South Brook valley outlet, and finally drained catastrophically through a spillway at Junction Brook. Marine limit at the coast was 60 m asl. Inland deltas at the head of Deer Lake and fine-grained sediment exposed in the Deer Lake valley show inundation below 45 m present elevation. This produced a narrow embayment extending at least 50 km inland from the modern coast and is named here as ‘Jukes Arm’. Dated marine macrofossils in the Humber Arm and lower Humber River valley, indicate the deltas at the head of Deer Lake formed about 12.5 ka.